A probabilistic framework for evaluating voltage unbalance mitigation by photovoltaic inverters. (December 2016) - Klonari, Vasiliki; Meersman, Bart; Bozalakov, Dimitar; Vandoorn, Tine L.; Vandevelde, Lieven; Lobry, Jacques; Vallée, François
Abstract: In three-phase Low Voltage (LV) networks, distributed photovoltaic (PV) units can contribute to voltage unbalance mitigation in case they are connected with the use of three-phase inverters integrating unbalance mitigation control schemes. This paper presents a probabilistic framework that simulates the time-varying action of voltage magnitude and unbalance mitigation schemes, locally implemented by PV inverters in LV feeders. The scope includes evaluating the effect of such strategies, in the context of a long-term techno-economic planning of the LV network, and characterizing LV network operation for increasing the observability of state estimation techniques applied in the Medium Voltage level. The presented framework evaluates the action of four distributed control schemes in an extensive range of possible network states assembled with the use of feeder-specific smart metering (SM) data. The simulation of a real LV feeder with distributed PV generation and historic SM measurements is presented. A control strategy that acts resistively towards the negative- and zero-sequence voltage components, without modifying the total nodal injected power (three-phase damping control strategy), results to be more effective compared with traditionally applied voltage control schemes.